Pengaruh Keyakinan Guru dan Pengembangan Profesional terhadap Integrasi Teknologi dalam Pembelajaran Akuntansi dengan Perceived Technology Skill sebagai Variabel Mediasi - Eka Indrawati; Kardiyem (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
In the era of the Industrial Revolution 4.0, the education system is required to transform digitally. The integration of technology in accounting learning at vocational schools needs to be carried out so that graduates can be adjusted to the needs of the industry. This study was conducted to analyze the influence of teachers' beliefs and professional development on technology integration, with perceived skills used as a mediation variable. This quantitative research involved 73 vocational school accounting teachers in Kebumen Regency who were selected through total sampling techniques. Data were collected through a closed-ended questionnaire and analyzed using SEM-PLS. Based on the results of the analysis, it was found that technology integration was significantly influenced by teachers' beliefs and technological skills. In contrast, professional development was not found to have a direct effect, but indirect influence through technological skills was declared significant. From these findings, it is suggested that technology training be provided in a practical manner and according to the needs of the field. Support from schools and policy makers also needs to be provided so that teachers' technology skills can continue to be improved. For further research, other contextual variables can be considered and a qualitative approach is suggested so that a deeper understanding can be obtained.